THE EMERGENCE ANIS DEVELOPMENT OF AGRICULTURAL AND ANIMAL ECONOMY IN IRAQ DURING PREHISTORIC TIMES - Hazim, Hussein Y. (Diyala Agricultural Sciences Journal, 2020)
The agricultural operations and domestication of animals Presented The basic factors and ingredients for The emergence and development of The agricultural and animal economy of Iraq during The Prehistoric Times in Particular, The head of the middle of the Century Bc. which is essential and extremely important given the establishment and development of these processes during. The research aimed to Study Those Processes that represent the real beginnings of the emergence and development of agricultural and animal economics in Iraq during Prehistoric times that represented this basic and important erainit. The study was conducted through two main axes of research, Such as the first axis, the emergence and development of agricultural operations and the most Prominent crops. As the Second axis represented the emergence and development of domestication of animals and the most Prominent domesticated animals. The study has been studied and information on The Subject has been extracted Through reports of the results of archaeological excavations of Iraqi sites that have seen agricultural operations and domestication of animals, especially those of economic benefit by finding charred seed residues for agricultural crops and domestic animal remains. through these data than were adopted by The study in The research, the mast Prominent agricnitural Crops and domesticated animal were identified that represented the first foundations and basic Pillars of the agricultural and animal economy in Iraq during that ancient time Period which laid the foundations and main ingredients for that economy in the Subsequent ages, indicating the manifestos that helped establish and develop that economy, environmental, Climatic and topographical processes appeared and were Printed and how These Conditions affected economic Production in that era.